A full year of the COVID‐19 pandemic with two infection waves and its impact on ischemic stroke patient care in Germany. (22nd August 2021) - Richter, Daniel; Eyding, Jens; Weber, Ralph; Bartig, Dirk; Grau, Armin; Hacke, Werner; Krogias, Christos
Abstract: Background and purpose: Many countries worldwide, including Germany, reported that the first wave of the coronavirus disease 2019 (COVID‐19) pandemic in early 2020 influenced the care of acute ischemic stroke (AIS) patients, but data are lacking for further pandemic wave periods. Methods: We conducted a nationwide, retrospective, cross‐sectional study of all hospitalized patients with the main diagnosis of AIS in 2019 and 2020. Primary outcomes were the number of hospitalizations for AIS, the application of stroke unit care, intravenous thrombolysis (IVT), and mechanical thrombectomy (MT), as well as the in‐hospital mortality during the different pandemic periods in 2020 compared to the corresponding periods in 2019. Secondarily, we analyzed differences in outcomes between patients with and without concurrent COVID‐19. Results: We included 429, 841 cases with AIS, of which 1268 had concurrent COVID‐19. Hospitalizations for AIS declined during both pandemic wave periods in 2020 (first wave: −10.9%, second wave: −4.6%). MT rates were consistently higher throughout 2020 compared to 2019, whereas the IVT rate dropped during the second wave period (16.0% vs. 17.0%, p  < 0.001). AIS patients with concurrent COVID‐19 frequently received recanalization treatments, with an overall MT rate of 8.4% and IVT rate of 15.9%. The in‐hospital mortality was high (22.8% vs. 7.5% in noninfected AIS patients, p  < 0.001). Conclusions: These findings demonstrate a smaller decline in hospitalizations for AIS in the more severe second wave of the COVID‐19 pandemic. AIS patients with and without concurrent COVID‐19 who did seek acute care continued to receive recanalization treatments in Germany. Abstract : There was a substantial decline in hospitalizations for acute ischemic stroke during the two COVID‐19 pandemic waves in Germany, with a smaller reduction during the second wave of the pandemic. Acute ischemic stroke patients still frequently received acute stroke care, including recanalization treatments during the entire year of 2020, irrespective of SARS‐CoV‐2 status.